1988
DOI: 10.1530/acta.0.1190075
|View full text |Cite
|
Sign up to set email alerts
|

Multiple pituitary hormone gradients from inferior petrosal sinus sampling in Cushing's disease

Abstract: Pre-operative bilateral simultaneous inferior petrosal sinus sampling with assessment of ACTH levels in the left and right sinuses and the periphery was performed in 9 patients with pituitary dependent Cushing's disease who were subsequently found at surgery to have basophil microadenomata. The novel observation of this study was the pattern of secretion of other pituitary hormones so that significant inter-sinus gradients \ m=ge\ 1.4:1 were seen for \g=b\-endorphin (2.8 \m=+-\1.3, mean \m=+-\ sem), PRL (4.2 \… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
31
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 18 publications
3
31
0
Order By: Relevance
“…This would suggest that a-MSHi concentrations in blood collected from the IPS ipsilateral to the adenoma could be related to tumoral release. Therefore, in the presence of an ACTH-secreting adenoma, together with a significant re lease of ACTH and p-ELI, as already reported by us [22,23] and by others 18,[25][26][27], in the IPS ipsilateral to the adenoma there is an increase of a-MSHi concentration in comparison to the contralateral IPS and the periphery. In contrast, in patients affected by OPD rather than CD no difference in a-MSHi concentration was found between IPSs and peripheral samples.…”
Section: Discussionsupporting
confidence: 77%
“…This would suggest that a-MSHi concentrations in blood collected from the IPS ipsilateral to the adenoma could be related to tumoral release. Therefore, in the presence of an ACTH-secreting adenoma, together with a significant re lease of ACTH and p-ELI, as already reported by us [22,23] and by others 18,[25][26][27], in the IPS ipsilateral to the adenoma there is an increase of a-MSHi concentration in comparison to the contralateral IPS and the periphery. In contrast, in patients affected by OPD rather than CD no difference in a-MSHi concentration was found between IPSs and peripheral samples.…”
Section: Discussionsupporting
confidence: 77%
“…To overcome this problem, it has been suggested to perform multiple samplings for ACTH in peripheral and IPSs blood [7], On the other hand, in certain cases the baseline evaluation of ACTH concentrations was not sufficient to correctly diagnose the cause of hypercortisolism and the administration of ACTH-releasing hormone (CRH) during IPSS has been shown to greatly improve the diagnostic accuracy of this test [2][3][4][5], Moreover, since it has been demonstrated that in ACTH-secreting adenomas there is a significant gra dient between the IPS ipsilateral and that contralateral to the adenoma (intersinus gradient, ISG) for P-endorphin, GH, PRL, FSH, LH, and a-subunit. basally [8][9][10][11] or after CRH stimulation [12,13], it has been proposed that the existence of a significant ISG for pituitary hormones other than ACTH may also indicate the presence of an ACTH-secreting adenoma. The results of previous stud ies, however, on the efficacy of multiple baseline ACTH evaluations, multiple hormone evaluation and CRH stim ulation during IPSS have led to conflicting conclusions, and the usefulness of these procedures during IPSS is still not well established.…”
mentioning
confidence: 99%
“…Additional difficulties arise be cause both pituitary and ectopic ACTH-secreting tumors may be radiologically occult [I], Selective venous sam pling for ACTH was proposed to differentiate these two variants of Cushing's syndrome [2,3], Simultaneous bilat eral petrosal sinus sampling has been introduced to im prove the diagnostic ability of this test in predicting tumor localization within the pituitary [4][5][6]. Recently, an oCRH stimulation test has been used to further increase both in terpetrosal and central/peripheral ACTH gradients [7][8][9], The additional determination of other pituitary hor mones, which increase in concomitance with ACTH after oCRH stimulation, seem to be of clinical relevance in cases in whom equivocal ACTH gradients are recorded [8,[10][11][12], We evaluated the validity of this tool in the differ ential diagnosis of ACTH-dependent hypercortisolism in 22 patients with Cushing's syndrome in whom laboratory findings were not conclusive and imaging studies failed to identify any pituitary lesion. In addition to ACTH, |i-endorphin has been assessed in order to evaluate the poten tial diagnostic usefulness of a combined determination of both hormones.…”
mentioning
confidence: 99%